PRODUKSI SERASAH HUTAN LARANGAN ADAT RUMBIO KECAMATAN KAMPAR UNTUK PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DI SMA KELAS X PADA KONSEP EKOSISTEM - Trisna Wati; Nursal '; Wan Syafii (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this research was to determine the Litter Production of The Rumbio Traditional Forest Bans Kampar District in September and November 2014. Research results are used for developing interactive learning media material to the concept Ecosystem Biogeochemistry Recycling. This research was carried out by two phases: the measurement of litter production and development stage interactive learning media. Litter production research conducted by using stratified random sampling survey, where there are 3 topography that valley, sloping and hilly. Each topography consists of 3 Litter trap with a size of 1x1 meters and is taken from the litter Litter trap container every 2 weeks for 2 months of the study. The parameters observed dropping litter composition of leaves, twigs, flowers and fruits. At this stage of the development of interactive learning media, carried out using ADDIE models. The results showed that the production of forest litter Prohibition of Indigenous Rumbio 426.6767 gr / m2 / week. Results of the research have been developed as an interactive learning media in the biogeochemical cycle of matter in the High School Class X.Keywords: Litter, Litter Production, Media Interactive Learning